Resilience Measurement and Enhancement of Subway Station Flood Disasters Based on Uncertainty Theory - Jingyan Liu; Shuo Zhang; Wenwen Zheng; Xinyue Hu (Applied Sciences)
To address the uncertainty of influencing factors in measuring the resilience of subway stations to flood disasters, this study introduces Unascertained Measurement Theory to assess the resilience of subway stations against flood disasters. Initially, the research involves a thorough examination and analysis of past subway flood disaster incidents, which elucidates the disaster system and its resilience processes, thereby facilitating the construction of a resilience analysis framework specific to subway stations. Subsequently, a measurement index system is developed to evaluate the resilience of subway stations against flood disasters, drawing upon relevant literature, and resilience levels are categorized according to established standards. Following this, an unascertained measurement model is formulated to assess the resilience of subway stations in the face of flood disasters. This model incorporates the development of an unascertained measurement function and an unascertained measurement matrix, yielding comprehensive results that inform the determination of resilience levels through credible degree assessment. Furthermore, the SPSSAU obstacle degree model is utilized to analyze the resistance factors that influence the resilience of subway stations to flood disasters, leading to the formulation of strategies aimed at enhancing this resilience. This approach offers novel insights into the measurement of subway station resilience in the context of flood disasters.